Efforts to Cultivate the Character of Responsibility in Students Through Religious Education at MTS Nurul Ali - Rowiyanto Rowiyanto; Maryono Maryono (Universitas Muhammadiyah Enrekang, 2023)
Given the demoralized information, there has been a loss of noble values inherent in our nation, such as honesty, politeness, togetherness, shame, responsibility, social care and so on. The purpose of this research is to seek to cultivate the character of responsibility in students through religious education at MTS Nurul Ali. This research method is descriptive qualitative. There were 5 informants, namely one Deputy Head of Madrasah, two religion teachers at Mts Nurul Ali, and two general subject teachers at Mts Nurul Ali. The results of this study for character building are forgotten by the school, so far too tempted to use academic goals, intellectual intelligence is encouraged, while emotional and spiritual intelligence is marginalized. Thus, if noble characters are embedded in students, noble character will automatically be reflected in student behavior in everyday life.